DIO3, the thyroid hormone inactivating enzyme, promotes tumorigenesis and metabolic reprogramming in high grade serous ovarian cancer. (31st March 2021) - Moskovich, Dotan; Alfandari, Adi; Finkelshtein, Yael; Weisz, Avivit; Katzav, Aviva; Kidron, Debora; Edelstein, Evgeny; Veroslavski, Daniel; Perets, Ruth; Arbib, Nissim; Kadan, Yfat; Fishman, Ami; et al.
Abstract: High grade serous ovarian cancer (HGSOC) is the most lethal gynecologic malignancy with a need for better understanding the disease pathogenesis. The biologically active thyroid hormone, T3, is considered a tumor suppressor by promoting cell differentiation and mitochondrial respiration. Tumors evolved a strategy to avoid these anticancer actions by expressing the T3 catabolizing enzyme, Deiodinase type 3 (DIO3). This stimulates cancer proliferation and aerobic glycolysis (Warburg effect). We identified DIO3 expression in HGSOC cell lines, tumor tissues from mice and human patients, fallopian tube (FT) premalignant lesion and secretory cells of normal FT, considered the disease site-of-origin. Stable DIO3 knockdown (DIO3-KD) in HGSOC cells led to increased T3 bioavailability and demonstrated induced apoptosis and attenuated proliferation, migration, colony formation, oncogenic signaling, Warburg effect and tumor growth in mice. Proteomics analysis further indicated alterations in an array of cancer-relevant proteins, the majority of which are involved in tumor suppression and metabolism. Collectively this study establishes the functional role of DIO3 in facilitating tumorigenesis and metabolic reprogramming, and proposes this enzyme as a promising target for inhibition in HGSOC. Highlights: DIO3 is expressed throughout ovarian cancer tumor evolution. DIO3 silencing resulted in tumor growth inhibition in vitro and in vivo . DIO3 facilitates tumorigenesis and metabolic reprogramming via depletion of intracellular T3 levels.